The Use of Teacher English Code Mixing in Teaching Interaction - Sinaga, Yolanda Agustina; Nasution, Jamaluddin (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
The study’s goal is to identify the various kinds and forms of code mixing, and also to analyze the reasons that affect the likelihood of code mixing in teaching interaction at SMA Free Methodist 2 Medan. Research methodology used in the study is a descriptive qualitative method in the application of case studies. The English teacher at SMA Free Methodist 2 Medan is the study’s subject. The research used Observation, interview and recording to collect data. The findings of this study indicated that there are three kinds of code mixing that the English teacher uses in class interactions, which were insertion, alternation congruent lexicalization. As for the forms of code mixing used in teaching interaction by the English teacher, which are word, sentence, and repetition. Where it can be seen that there are 15 utterances which are included in the kinds of code mixing and 13 utterances which are included in the forms of code mixing. There are also the reasons that influence the occurrence of code mixing in teaching interaction is talking about a particular topic in the class that requires the teacher to use code-mixing, the teacher does several repetitions in a sentence to clarify the words being discussed so that students can understand the topic, the teacher decides to speak in another language for a while, the teacher wants to convey a message from this topic uses code-mixing, the teacher wants to focus student’s attention by using code mixing, and the teacher wants to show respect for the students.